2019
DOI: 10.1136/sextrans-2018-053835
|View full text |Cite
|
Sign up to set email alerts
|

High burden of chlamydia and gonorrhoea in pharyngeal, rectal and urethral sites among Thai transgender women: implications for anatomical site selection for the screening of STI

Abstract: ObjectiveComprehensive data on Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections to guide screening services among transgender women (TGW) are limited. We studied the burden of CT/NG infections in pharyngeal, rectal and urethral sites of Thai TGW and determined missed CT/NG diagnoses if selected site screening was performed.MethodsThai TGW were enrolled to the community-led test and treat cohort. CT/NG screening was performed from pharyngeal swab, rectal swab and urine using nucleic acid amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…It might be the case that those at the highest risk of rectal infections were more likely to accept rectal screening; however, there were no differences in rectal screening acceptance based on reporting anal intercourse in the past three months. A recent study of Thai TGW found that rectal screening produced the highest yield of positive NG/CT infections [10], implying that rectal screening will be vitally important to reduce NG/CT incidence and prevalence. Future studies should assess reasons for refusal of rectal screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be the case that those at the highest risk of rectal infections were more likely to accept rectal screening; however, there were no differences in rectal screening acceptance based on reporting anal intercourse in the past three months. A recent study of Thai TGW found that rectal screening produced the highest yield of positive NG/CT infections [10], implying that rectal screening will be vitally important to reduce NG/CT incidence and prevalence. Future studies should assess reasons for refusal of rectal screening.…”
Section: Discussionmentioning
confidence: 99%
“…Current STI screening recommendations in South Africa are based on syndromic surveillance and management [6]. Much of the STI screening that is conducted with MSM and TGW is by blood or urine specimens, but in some studies of MSM and TGW, there is considerably higher prevalence of rectal STIs than urethral STIs or syphilis [7‐9] and multi‐site screening has been shown to substantially increase the yield of positive tests [10].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the gonorrhoea positivity of urogenital specimens ranged from 0.1% (among 764 women from drop-in centres in Thailand) to 2.8% (among 406 STI clinic attendees at multiple sites in the USA), positivity of pharyngeal specimens ranged from 3.5 to 37.3% across studies (with positivity of 8.1-9.8% in the two largest studies from Thailand and the USA). [72][73][74][75] Positivity among rectal specimens ranged from 6.3 to 43% (9.6-11.8% in the Thailand and USA studies). [72][73][74][75][76] Two studies that did not mention the anatomic site of specimen collection found a prevalence among transgender women of 2.1% (among 63 young adults in the USA) and 4% (among 77 STI clinic attendees in Australia).…”
Section: Transgender Personsmentioning
confidence: 94%
“…[72][73][74][75] Positivity among rectal specimens ranged from 6.3 to 43% (9.6-11.8% in the Thailand and USA studies). [72][73][74][75][76] Two studies that did not mention the anatomic site of specimen collection found a prevalence among transgender women of 2.1% (among 63 young adults in the USA) and 4% (among 77 STI clinic attendees in Australia). 77,78 Although data on transgender men are even more scarce, available data hint at high gonorrhoea prevalence.…”
Section: Transgender Personsmentioning
confidence: 94%
“…Bacterial STI prevalence varies among transgender women and is based largely on convenience samples. Despite limited data, international and U.S. studies have indicated elevated incidence and prevalence of gonorrhea and chlamydia among transgender women similar to rates among cisgender MSM (346)(347)(348). A recent study using data from the STD Surveillance Network revealed that the proportions of transgender women with extragenital chlamydial or gonococcal infections were similar to those of cisgender MSM (349).…”
Section: Transgender Womenmentioning
confidence: 99%